2015
DOI: 10.1186/s13014-015-0448-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated irradiation in elderly patients with breast cancer after breast conserving surgery and mastectomy : Analysis of 205 cases

Abstract: BackgroundSeveral randomized trials and meta-analyses confirmed a wide benefit of radiotherapy (RT), both after breast conserving surgery (BCS) and mastectomy. However, many elderly women don't receive RT. Hypofractionated (HF) RT allows « simplified » and more accessible treatments with equivalent results to classic RT in three large randomized trials. However, there are few available data on HF-RT for nodal irradiation, as well as for the boost.MethodsWe evaluated patients treated for IBC by HF-RT between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…This meta-analysis indicated that HFRT and CFRT were equally effective with respect to overall survival (OS), disease-free survival (DFS), locoregional recurrence (LRR), and distant metastasis (DM) after breast mastectomy. In recent small retrospective cohort studies, HF PMRT was shown to be effective with acceptable toxicity [38][39][40][41]. In a recent phase 2 trial [42], 67 women with clinical stage II to IIIa breast cancer who received a HF PMRT regimen of 36.6 Gy over 11 fractions to the chest wall and the draining regional lymph nodes with a scar boost of 4 fractions of 3.33 Gy revealed that after a median follow-up of 32 months, patients with isolated ipsilateral chest wall tumor recurrences were 3.0%, the 3-year estimated overall survival was 92.0% (95% CI, 78.9~97.1), the 3year estimated local recurrence-free survival was 89.2% (95% CI, 74.8~95.6), the 3-year estimated distant recurrence-free survival was 90.3% (95% CI, 79.7~95.6), and low toxicity was reported.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis indicated that HFRT and CFRT were equally effective with respect to overall survival (OS), disease-free survival (DFS), locoregional recurrence (LRR), and distant metastasis (DM) after breast mastectomy. In recent small retrospective cohort studies, HF PMRT was shown to be effective with acceptable toxicity [38][39][40][41]. In a recent phase 2 trial [42], 67 women with clinical stage II to IIIa breast cancer who received a HF PMRT regimen of 36.6 Gy over 11 fractions to the chest wall and the draining regional lymph nodes with a scar boost of 4 fractions of 3.33 Gy revealed that after a median follow-up of 32 months, patients with isolated ipsilateral chest wall tumor recurrences were 3.0%, the 3-year estimated overall survival was 92.0% (95% CI, 78.9~97.1), the 3year estimated local recurrence-free survival was 89.2% (95% CI, 74.8~95.6), the 3-year estimated distant recurrence-free survival was 90.3% (95% CI, 79.7~95.6), and low toxicity was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies [39][40][41] have shown that hypo-fractionated PMRT is safe and effective and can provide similar tumor control rate as standard 25 fractions radiotherapy for carefully selected post-mastectomy patients. It is also much more convenient for the patients and caregivers and can significantly cut treatment costs [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized trials confirmed the effectiveness of adjuvant chemotherapy and radiotherapy in improving survival for older women with early-stage breast cancer [19-21]. Under treatment of elderly breast cancer was demonstrated in several studies and typically resulted in worse clinical outcome [14,18].…”
Section: Discussionmentioning
confidence: 99%